2008
DOI: 10.3858/emm.2008.40.2.186
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of TNF-induced necrotic cell death by rottlerin through a Nox1 NADPH oxidase

Abstract: Previous studies have demonstrated that rottlerin, a specific PKCδ inhibitor, potentiates death receptormediated apoptosis through a cytochrome c-dependent or -independent pathway. However, its ability to regulate necrotic cell death, as well as the underlying mechanism, remains unknown. We found that in murine fibrosarcoma L929 cells, treatment with rottlerin protected the cells against TNF-induced necrosis, whereas it sensitized the cells to apoptosis induced by co-treatment with Hsp90 inhibitor geldanamycin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 29 publications
(35 reference statements)
1
12
0
Order By: Relevance
“…Slug suppression by RNA interference markedly enhanced H 2 O 2 -induced apoptosis in RA FLS, and this was mediated by increased caspase-3 activation. H 2 O 2 -induced cell necrosis could also have contributed to FLS death in our experiment (Byun et al, 2008), but obvious influence of Slug suppression on FLS apoptosis has been demonstrated by apoptosis specific ELISA and caspase-3 activation assay. Because experiments comparing RA FLS with osteoarthritis FLS were not performed, we don't know whether these results are specific to RA FLS and it is unclear whether these Slug mediated apoptotic regulation is also operating in osteoarthritis or normal FLS.…”
Section: Discussionmentioning
confidence: 62%
“…Slug suppression by RNA interference markedly enhanced H 2 O 2 -induced apoptosis in RA FLS, and this was mediated by increased caspase-3 activation. H 2 O 2 -induced cell necrosis could also have contributed to FLS death in our experiment (Byun et al, 2008), but obvious influence of Slug suppression on FLS apoptosis has been demonstrated by apoptosis specific ELISA and caspase-3 activation assay. Because experiments comparing RA FLS with osteoarthritis FLS were not performed, we don't know whether these results are specific to RA FLS and it is unclear whether these Slug mediated apoptotic regulation is also operating in osteoarthritis or normal FLS.…”
Section: Discussionmentioning
confidence: 62%
“…TNF-TNFR complex has also been shown to enhance NADPH oxidase activity promoting a burst of oxidative stress and leading to necrotic cell death (141,142).…”
Section: Cross-linking Of Tnf and Tnfr Type I Dependent Pathwaymentioning
confidence: 99%
“…DN-p38 MAPK mutant construct was kindly provided by Dr Surh (Seoul National University, Seoul, Korea) . DN-PKCd adenovirus was provided by Dr Hur (Chungnam National University, Daejeon, Korea) (Byun et al, 2008). Cells were transfected according to the manufacturer's instructions with Lipofectamine 2000 transfection reagent obtained from Invitrogen (Carlsbad, CA, USA).…”
Section: Methodsmentioning
confidence: 99%